Synthesis and characterization of hydrophobic starch nanoparticles - Caryn, Tan Sze Yee (Universiti Malaysia Sarawak (UNIMAS), 2015)
Sago starch is derived from one of the oldest tropical crops; sago palm (Metroxylon sagu) and have been widely exploited by men. As they are easily found at low cost with biodegradability properties, sago starch has been of great emphasized to act as a drug carrier. In this study, sago starch was subjected to chemical modification using esterification process to exhibit hydrophobicity using different parameters such as concentration, temperature and duration of reaction. Sago starch dissolved in 50mL of DMF with a ratio of 1:1.5 to oleic acid at the temperature of 100 ºC with a reaction time of 2 hours in the presence of DMAP catalyst yield the highest degree of substitution at 0.12. The existence of a carbonyl peak at 1724 cm-1 in the FTIR spectrum confirmed the successful modification by means of introducing the fatty acid unto the native sago starch. The obtained starch oleate was dissolved in 0.8 wt% NU solution and added drop wise into an absolute ethanol solution to yield hydrophobic starch nanoparticles. The morphology of the hydrophobic starch nanoparticles were studied using SEM.